New media in late 20th-century art. - Rush, Michael (London : Thames and Hudson, 1999)
All the major movements in modern art, from Cubism and Dada to Performance and Installation, were initiated in reaction to the centuries-old tradition of representing the world visually in recognizable ways. Reflecting intellectual, scientific and technological developments, artists abandoned strict adherence to traditional materials and embraced any means which best served their purposes, redefining art and the countless ways in which it can be made and experienced. This pioneering book traces the history of new media in art and includes discussions of film making, video, digitally manipulated photography, virtual reality, installation and performance by artists such as Nam June Paik, Vito Acconci, Marina Abramovic, Pipilotti Rist, Bill Viola and others whose seminal works have radically transformed world art.
Abramovic, Marina ; Acconci, Vito ; Ackerman, Chantal ; Almy, Max ; Anderson, Laurie ; Baldessari, John ; Balla, Giacomo ; Ballard, Norman ; Barney, Matthew ; Barry, Judith ; Beavers, Robert ; Benning, Sadie ; Beuys, Joseph ; Birnbaum, Dara ; Brook, Peter ; Burden, Chris ; Burgin, Victor ; Cahen, Robert ; Campus, Peter ; Chevalier, Miguel ; Cho, Seoungho ; Chong, Ping ; Cottingham, Keith ; Davis, Douglas ; Doherty, Willie ; Donegan, Cheryl ; Downey, Juan ; Duchamp, Marcel ; Eisenstein, Sergei ; Emshwiller, Ed ; Export, Valie ; Feingold, Ken ; Fischer, Konrad ; Forgacs, Peter ; Froese, Dieter ; Furuhashi, Teiji ; Gaumnitz, Michaël ; Gillette, Frank ; Glass, Philipp ; Godard, Jean-Luc ; Goldenberg, David ; Gordon, Douglas ; Graham, Dan ; Graham, Rodney ; Gromala, Diana ; Hamilton, Richard ; Hatoum, Mona ; Hershman Leeson, Lynn ; Hill, Gary ; Hyber, Fabrice ; Idemitsu, Mako ; Jacobs, Ken ; Jenkins, Amy ; Jesurun, John ; Jonas, Joan ; Kubota, Shigeko ; Latham, William ; Lepage, Robert ; Lord, Chip ; Lublin, Lera ; Lucas, Kristin ; Lucier, Mary ; Markopolous, Gregory J. ; McQueen, Steve ; Mendieta, Ana ; Miskell, Brad ; Modin, Bengt ; Moholy-Nagy, Laszlo ; Molnar, Vera ; Moore, Stefan ; Mullican, Matt ; Muybridge, Eadweard ; Nauman, Bruce ; Noll, Michael ; Odenbach, Marcel ; Ono, Yoko ; Orlan ; Oursler, Tony ; Paik, Nam June ; Piene, Otto ; Piper, Adrian ; Plessi, Fabrizio ; Prince, Richard ; Rapp, Ray ; Rauschenberg, Robert ; Reilly, John ; Richter, Gerhard ; Rist, Pipilotti ; Rosenbach, Ulrike ; Rush, Michael ; Sandin, dan ; Schneemann, Carolee ; Schwartz, Lillian ; Seaman, Bill ; Shaw, Jeffrey ; Shiomi, Mieko (Chieko) ; Simon, John ; Sims, Karl ; Sjolander, Ture ; Smith, Bradford ; Smith, Mike ; Smith, Stephanie ; Snow, Michael ; Sokurov, Alexandr ; etc.
boek